Preliminary test: Evaluation and selection of tomato (Lycopersicon esculentum Mill.) varieties resistant to drought and powdery mildew - Massimi, Mohunnad; Radocz, Laszlo (Acta Agraria Debreceniensis, 2021)
Powdery mildew (Leveillula taurica) and (Oidium neolycopersici) are two harmful fungi that invade the tomato (Lycopersicon esculentum Mill.) plant and grow in dry conditions. Under the influence of polyethylene glycol 6000 at a concentration of 12%, the total seedlings fresh weight, total seedlings dry weight, seedling growth rate of one seedling, seedling length, and tissue water content percentage for three tomato varieties were assessed. Despite the superiority of the (Mobil) tomato variety in terms of numerical values, the results revealed no significant differences between varieties. As a result, (Mobil) has greater vigor under environmental drought stress of lower osmotic stress than other tomato varieties. More work is required to evaluate the research selection of varieties resistant to biotic stresses in dry areas, such as powdery mildew disease.